2015
DOI: 10.1590/1809-4430-eng.agric.v35n1p144-153/2015
|View full text |Cite
|
Sign up to set email alerts
|

Color change and quality response of ‘lane late’ orange submitted to degreening process

Abstract: ABSTRACT:This study aimed at evaluating the effects of ethylene on peel color and compositional changes in 'Lane late' orange stored under refrigerated and ambient conditions. Physiologically mature, but green-peeled, oranges were exposed to ethylene gas under room temperature and high relative humidity for 24 hours. Storage chamber was ventilated with fresh air after 12 hours to mitigate consequences derived from fruit respiration. Both nondestructive analysis, such as peel color (hue angle, chromaticity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…The correlations also indicated that at higher storage temperature, weight loss and SS are greater and firmness and TA are lower, which is consistent with the results of Machado et al (2015), who found that the speed of enzymatic reactions increases exponentially with increasing temperature and is responsible for these physico-chemical changes in orange fruits. Amarante et al (2008) The correlations between the variables listed in Table 3 indicate that at higher production zone altitudes, there is a higher SS content and lower values for weight loss and skin and pulp firmness during the post-harvest period.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The correlations also indicated that at higher storage temperature, weight loss and SS are greater and firmness and TA are lower, which is consistent with the results of Machado et al (2015), who found that the speed of enzymatic reactions increases exponentially with increasing temperature and is responsible for these physico-chemical changes in orange fruits. Amarante et al (2008) The correlations between the variables listed in Table 3 indicate that at higher production zone altitudes, there is a higher SS content and lower values for weight loss and skin and pulp firmness during the post-harvest period.…”
Section: Resultssupporting
confidence: 89%
“…The increase in SS during ripening is caused by organic acids turning into sugars or degrading through respiration (Machado et al, 2015). Loss of firmness during ripening is caused by increased enzymatic activity, which degrades pectins (Parra-Coronado et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Even in fruits exposed to ethylene and coated with wax, this characteristic was observed, because, despite the change in peel color, these fruits showed higher hue values due to the use of coating. Similar results were reported by Machado et al (2015), who observed decrease in the values of hue angle from 124 to 100, analyzing 'Lane late' oranges subjected to the degreening treatment.…”
Section: Resultssupporting
confidence: 89%
“…Among other several factors, climatic conditions play a defining role in peel coloration of citrus 61 whereas in sub-tropical regions citrus peel yellow coloring takes place with drop of temperature at 12.8°C along with soil temperature near to 12°°C. 62 In this work, temperature was dropped in October to initiate color-break and earlier commenced of winter at Sargodha had also widened a gap in diurnal temperature.…”
Section: Resultsmentioning
confidence: 99%